Political Education in Action: Social Studies Majors’ Insights on Building Quality Education and Just Institutions - David, Rowena May; Maroma, Adrian (Journal of Interdisciplinary Perspectives, 2025)
This research discussed the political consciousness and civic involvement of students pursuing a Bachelor of Secondary Education in Social Studies at Bulacan State University and how they will use their role as future teachers to educate an enlightened citizenry. There was a high level of political consciousness found in the respondents, but only a moderate level of civic participation. This gap emphasizes the essential demand for pedagogical approaches that enable students to turn knowledge into action. Dramatic contrasts across year levels highlight the imperatives of a developmental strategy for civic education, sharpening more and more awareness and engagement in politics and society. Knowledge, while a necessary foundation, is prioritized by this study as not enough on its own to bring about effective civic participation. The future teachers learn optimally if they are given genuine opportunities to interact with the life of society, think critically about their experiences, and think actively about how they can make meaningful contributions to nation-building. To satisfy this need, the Social Studies program must put theory into practice—encouraging not just intellectual development, but ethical and emotional growth as well. In this way, it prepares future teachers to be active, responsible, and transformative citizens. Lastly, this reaffirms the core function that education plays to build a more equitable and democratic society.